Ability to solve the problems of high orders for students of University (Journal of the College of Education for Women, 2019)
It is known that life is as series of variety of difficult problems that individual looksforward to overcome so as to achieve adaptation and to reach the desired aims .The transitionof the students from the school stage to the stage of the university is actually regarded adramatic change where students face when they enter university life that differs from whatthey lived in secondary school.The executive functions are considered the main element that participate in solving theproblems of high orders , because it involves the mental abilities that assist individual tothink and initiative as well as solving problems .These functions include operational planning and the activated memory and inhibition ofquality impulsivity.The researcher has seriously dealt with the problem by passing with the initial universitystudy phase .It's worthy to say that she has faced many changes and difficulties which are related tocognitive processes and planning to accomplish new tasks that have become claim towardsthem.As well as , at the transition phase from the primary school to the postgraduate studies.The importance of current research is based on the significance of the variable which istaken , as the ability to solve the problems of high orders that will facilitate for individualthe performance of positive social behavior and the interaction with others.The researcher also , according to her own knowledge , doesn't find any Arab study or Iraqione that has dealt with the variable of ability to solveproblems of high orders , that matteradds to the current research originality and importance in opening up new prospects for thefuture studies . The research has to achieve the following goal :-Knowing and measuring the ability to solve the problems of high orders of the universitystudents.The application of the Tower of London test was done on a sample consisting of 200 studentsfrom the University of Baghdad - Jadiriya complex students, and after using appropriatestatistical methods . Results have concluded that university students have the ability to solvethe problems of high orders .